2000
DOI: 10.1177/107755870005700402
|View full text |Cite
|
Sign up to set email alerts
|

Selection Bias in HMOs: A Review of the Evidence

Abstract: Early reviews found that health maintenance organizations (HMOs) attracted healthier beneficiaries in the Medicare program and healthier employees in the market for employer-based insurance. This review finds that HMOs still attract healthier Medicare beneficiaries, that HMOs no longer attract healthier employees, and that HMOs attract healthier Medicaid recipients. This review also found conflicting evidence about whether Medicare HMOs are overpaid, no evidence that HMOs are overpaid in the market for employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 20 publications
6
62
0
Order By: Relevance
“…9 Patient selection may also account for the higher turnover rate by HMO enrollees, because patients who have formed strong relationships with their physicians are less likely to join a managed care plan. 39 These findings are largely consistent with other local and regional studies that compare the primary care experience of HMO and FFS users. Using a random sample of consumers in a defined geographic area of Washington, DC, Starfield et al found that comprehensiveness as measured by services available was reported to be significantly better by consumers associated with facilities that were primarily capitated than by consumers whose facilities were primarily FFS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…9 Patient selection may also account for the higher turnover rate by HMO enrollees, because patients who have formed strong relationships with their physicians are less likely to join a managed care plan. 39 These findings are largely consistent with other local and regional studies that compare the primary care experience of HMO and FFS users. Using a random sample of consumers in a defined geographic area of Washington, DC, Starfield et al found that comprehensiveness as measured by services available was reported to be significantly better by consumers associated with facilities that were primarily capitated than by consumers whose facilities were primarily FFS.…”
Section: Discussionsupporting
confidence: 81%
“…20,22 While an HMO improves access to care for those previously without it, [41][42][43] HMO enrollees have greater difficulty gaining access to care than enrollees in traditional FFS health plans. 39 Safran et al 22 also found diminished organizational access for HMO patients. The organizational barrier could be the result of oversubscription by the physicians or of negative incentives to see capitated patients.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted mortality rates for age, sex, and comorbidity, however, and patients belonging to an HMO were usually found to be healthier than patients with FFS insurance. 42,43 We found, though, that patients with commercial HMO insurance and those with commercial FFS insurance had similar measures on the Charlson-Deyo comorbidity index. We did not have detailed information on the specific types or intensities of treatments received, nor on the overall quality of care rendered, so it is also possible that the health care that FFS and HMO patients received differed in other important ways not captured by our study.…”
Section: Discussionmentioning
confidence: 58%
“…As a result, this plan may have been more attractive to those SSI beneficiaries who had been using specialty providers in the past or who anticipated needing easy access to such providers in the future. Numerous studies have found that plans with rigid gatekeeping systems have favorable selection (Hellinger 1995).…”
Section: Factors Likely Affecting Choice and Risk Selectionmentioning
confidence: 99%